2020
DOI: 10.1155/2020/8866697
|View full text |Cite
|
Sign up to set email alerts
|

Seepage Property of Crushed Mudstone Rock in Collapse Column

Abstract: The karst collapse column composed of crushed rocks and fine argillaceous or clay particles is easy to form the fissure channels between the coal seam working face and the confined limestone aquifer under mining and causes water inrush disasters with the loss of underground water resource, economic losses, and casualties. It is of great necessity to understand the seepage properties of crushed rock in karst collapse column for the prevention of water inrush and the protection of underground water resource. A s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…A large number of applications in civil engineering relate to groundwater flow, such as slope stability [21][22][23]; surface/subsurface soil erosion and sediment transport [24][25][26]; dam safety, including piping under and through dams [27][28][29][30][31][32]; groundwater contamination [33][34][35][36]; stability of artificially freezing ground [37,38]; sustainable management of water resources [39][40][41][42]; interaction between groundwater and surface water [43,44]; and karst collapse pillars [45][46][47].…”
Section: Introductionmentioning
confidence: 99%
“…A large number of applications in civil engineering relate to groundwater flow, such as slope stability [21][22][23]; surface/subsurface soil erosion and sediment transport [24][25][26]; dam safety, including piping under and through dams [27][28][29][30][31][32]; groundwater contamination [33][34][35][36]; stability of artificially freezing ground [37,38]; sustainable management of water resources [39][40][41][42]; interaction between groundwater and surface water [43,44]; and karst collapse pillars [45][46][47].…”
Section: Introductionmentioning
confidence: 99%
“…Column. XRD (X-ray diffraction) is a diffraction pattern which is obtained by diffraction of X-rays in crystals [24,25]. The mineral component of collapse column is measured by the X-ray diffraction test (XRD), which is shown in Figure 2.…”
Section: Mineral Component Of Collapsementioning
confidence: 99%
“…Research results showed that the effective porosity, particle crushing characteristics, and seepage characteristics of the crushed limestone were not only related to the degree of compaction and the particle size of the mixture but also to the arrangement and initial pore structure. Zhang et al analyzed the effects of the consolidation pressure, initial moisture content, and confining pressure on the permeability of the filling materials in the karstic collapse column [14,15]. It was found that the permeability coefficient of collapse column fillings decreases with an increase of the consolidation pressure and a decrease of the initial moisture content.…”
Section: Introductionmentioning
confidence: 99%